(3GdYRjRj GdeMdjs - (3YRjR Gddg (B((3YdGA GdOjf(B) (3Hf Gdcejdj GdefUhQj Hf GdoeNdWI GdeGdcj, eMeO Hf YHO Gddg Hf MSfs
(3ChdgG (B:s
(3WQa GdCNHGQ, hXQa GdCTYGQ, hGdeaGcgGJ hGdfhGOQ, edJbWkG Pdc ef GdOaGJQ s
(3BNQgG (B:s
(3bGd ef YQa Gddg cja jYUjg, hef YQa GdTjWGf cja jWjYg, hef Cjbf HGdehJ cja jgfjg GdYjT s
(3HChdgG bQGAI eDQNI SfI (B1209(3g`s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B100 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B35 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1140s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdCOHs